Administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand - Louharungpisit, Ancharaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this research aware 1) to study the administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand,2) to study the factors affecting the administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand and 3) to propose administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand. This research is a qualitative research using descriptive statistics. The research results showed that: (1) According to the study of the administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand, it was found that administrative policy for improving quality of life of the senior citizen at the social level is moderate. While improving the quality of the senior citizen at other levels (community level, organization level, interpersonal level and personal level) is very high. The needs of the senior citizen are as follows:1) the need for place and facilities 2) the need for tangible and intangible things from government agencies or communities 3) the need to participate in fitness and recreation activities. (2) The study of factors affecting the administrative policy for improving quality of life of the senior citizen in the eastern province of Thailand found that health officials have provided good knowledge about the time and place that the senior citizen can go to receive medical care services, the staff provides knowledge about proper exercise, and provides various facilities in exercise. The senior citizen want to have a place for exercise near their home while some senior citizens want a place to exercise in department stores. Finally, the public health authorities have provided good recreational facilities for the senior citizen in his community. (3) Guidelines for the management of development of quality of life for the senior citizen in the eastern provinces of Thailand found that this policy will promote the integration of relevant departments in system management in the community, provide a center or fitness facility that is suitable for all age groups and develop a form of physical activity and exercise that must be appropriate and consistent with the lifestyle of the community. In particular the policy integration to create a system to manage and promote physical activity in the community according to public policies that are defined in accordance with the national strategy which must be integrated at the ministry level in order to make policy driven into truly integrated operations. Both in the areas of public health agencies, local administrative organizations, tourism and sports, institutions of physical education, educational institutions, the Office of Social Development and Human Security, agencies related to urban and transport planning, educational institutions, tourism and sports and government agencies. Article history: Received 15 June 2019 Revised 10 July 2019 Accepted 12 July 2019 SIMILARITY INDEX= 0.00 %